PELATIHAN MICROSOFT WORD UNTUK MENINGKATKAN KETERAMPILAN DAN PEMBERDAYAAN ANGGOTA PKK - Muhammad, Muhammad Hery Santoso; Herni Utami Rahmawati; Jatmiko Indriyanto; Mutiasari; Nurul Hasanah (Universitas Mataram, 2024)
Lack of knowledge about how to use Microsoft Word has a negative impact on the efficiency and productivity of PKK members in Purwokerto Kulon Village. This hinders the production of important documents, reports and correspondence needed to carry out their activities. In addition, these limitations also reduce their opportunities to participate in broader administrative activities, hindering the empowerment and development of individuals and the community as a whole. PKK members focus on improving the welfare of families and communities through social, educational and health activities. Mastery of Microsoft Word is important for them because it makes it easier to create documents and increases efficiency in administrative tasks. The aim of Microsoft Word training for PKK members is to improve technological skills, administrative efficiency in organizational tasks, and support their empowerment in broader activities. The training method in community service is a combination of lectures, demonstrations and direct practice which begins with the distribution of a pre-test, implementation of training and ends with the distribution of a post-test. The target of this community service is the 18 PKK members of the Purwokerto Kulon subdistrict. A whole series of community service activities have been carried out. Counseling and training were successfully implemented and there was a significant increase in PKK members' knowledge regarding Microsoft Word. They are more adept at creating, editing documents, and are able to utilize features they were previously unable to master. When the pre-test was carried out, 27% of PKK members had mastered Microsoft Word, when the post-test was carried out there was an increase to 95% of members mastering the application. Community service activities were carried out according to plan and succeeded in increasing the knowledge of PKK members.